Why have band theorists been so successful in explaining and predicting novel superconductors?. (27th February 2019) - Mazin, I I
Abstract: In this contribution to the J. Phys.: Condens. Matter memorial issue in honor of Sandro Massidda I reflect on a phenomenon Sandro had been a part of. While theoretical condensed matter physicists have made, over the years, exciting and most elegant contributions to the theory of superconductivity (which, in and by itself, is one of the most beautiful constructs in theoretical physics), some of them of utmost importance, they have had less success in predicting and explaining superconducting states and mechanisms in specific materials. More down-to-earth computational materials scientists, who often go by the moniker 'band theorists', have been much more successful in applying (usually other people's) ideas in such circumstances. In this essay I give some examples, largely drawn from my own experience, and speculate on their meaning.